2016
DOI: 10.1016/j.electacta.2016.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemistry at free-standing carbon nanotubes electrodes

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1. ISE member. Abstract.A versatile and low-cost methodology for fabricating free-standing carbon nanotubes (CNT) electrodes for electrochemical and spectroelectrochemical applications is described. The uniformity, flexibility and resistance to bending of these films make them one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…However, the other face (side B) remains unmodified; the main peaks observed are related to C and O from the SWCNT film, and Al and Si probably related to the presence of dust deposited during the fabrication and/or functionalization processes. Therefore, according to the results presented in this work and taking as reference a previous work [50], it can be concluded that only one face of the FS-SWCNT electrode has been independently functionalized with AgNPs without interference between both faces, fact that opens new gates for simple design of Janus materials.…”
Section: Agnps Electrodeposition On Fs-swcnt Electrodessupporting
confidence: 66%
See 2 more Smart Citations
“…However, the other face (side B) remains unmodified; the main peaks observed are related to C and O from the SWCNT film, and Al and Si probably related to the presence of dust deposited during the fabrication and/or functionalization processes. Therefore, according to the results presented in this work and taking as reference a previous work [50], it can be concluded that only one face of the FS-SWCNT electrode has been independently functionalized with AgNPs without interference between both faces, fact that opens new gates for simple design of Janus materials.…”
Section: Agnps Electrodeposition On Fs-swcnt Electrodessupporting
confidence: 66%
“…The fabrication of SWCNT and FS-SWCNT electrodes ( Fig. S1 in Supporting Information), used as working electrodes, was carried out base on the methodology described in previous works [50,58,59]. SWCNT solution used for preparing both SWCNT and FS-SWCNT electrodes was dispersed using a CY-500 tip-sonicator (Optic ivymen System).…”
Section: Fabrication Of Swcnt and Fs-swcnt Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties can change as function of the metal, size, shape, or number of components of the NPs and are different from the bulk or their constituents because the surface of the NPs is structurally and compositionally different . Synthesis of metal NPs can be accomplished by different methods, such as chemical reduction, seed‐mediated, photochemical, electrochemical, sonochemical, lithography, galvanic replacement, thermal evaporation, radiolysis, sol–gel, laser ablation, chemical vapor deposition, microwave assisted, and biological assisted . The selection of the synthesis method, concentration of the reagents, and other experimental parameters, such as pH, temperature, and so forth, allows us to obtain NPs with specific size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…14 On the other hand, asymmetric decoration or singleface modification consists of two steps, the first one associated with the formation of the membrane, and the second step in which Janus structure is achieved by the functionalization of the membrane. Preparation of Janus membranes by crosslinking, 15 photo-degradation, 16 vapor processing, 17 coating, 18 electrochemical deposition, 19 floated deposition 20 and sequential surface modification 21 are examples of asymmetric decoration route. Traditionally, several drawbacks have been observed in a wet process, 11 as the capillary limitation in which the solution gradually penetrates through the membrane pores leading to the same modification on both sides, i.e., different functionalization of the two faces of the membrane in a unique step becomes impossible.…”
Section: Introductionmentioning
confidence: 99%